Monitoring Penyiraman Aglonema Lulaiwan Otomatis Berbasis IoT Dengan Sensor Soil Moisture dan DHT11 Menggunakan Aplikasi Telegram - Zulfachmi Zulfachmi; Aggry Saputra; Juliadi Juliadi (LPPM Universitas Putera Batam, 2023)
IoT-Based Automated Aglonema Lulaiwan Watering Monitoring With Soil Moisture and Dht11 Sensors Using the Telegram Application is designed to assist users in monitoring and watering plants. This study aims to inform the user that the plants lack water or not and in watering so as not to overwater. This study uses devices such as Base NodeMCU ESP8266, NodeMCU ESP8266, Sensor Soil Moisture, DHT11, Relay, Box 9V Battery, 9V Battery, LCD16x2 I2C, Mini Pump and telegram application, This Mini Pump works if the soil moisture is below 50%. This Aglonema plant watering system works automatically which uses a Soil Moisture sensor to measure soil moisture, DHT11 to check the temperature around the plant, The relay functions to turn off the Mini Pump, The Mini Pump works as a dispensing of water to the plants and the telegram application functions to provide notifications to check soil moisture and temperature around the plants. With this automatic watering system can help users determine soil moisture.